Learning how to make room to gendered practices in contexts of teaching english as a foreign language : a multiple case study (2017)
"This study describes a learning experience carried out with English teachers who took an optional course aimed at raising gender awareness and understanding the relationship this has with the English teacher?s contexts and practices. This course was offered in a Masters Program of Applied Linguistics to Teaching English as a Foreign Language (TEFL) taught at a state university in Bogotá. As part of the course, students/teachers (STs) were engaged in research activities in their actual teaching scenarios. Consequently, three STs accepted to do their small-scale research projects in collaboration with one of the Teacher of Teachers (ToTs) of the course." -- Tomado del Formato de Documento de Grado.